2021
DOI: 10.1007/s10029-021-02450-4
|View full text |Cite
|
Sign up to set email alerts
|

Identification of fifty-seven novel loci for abdominal wall hernia development and their biological and clinical implications: results from the UK Biobank

Abstract: Purpose Familial aggregation is known for both hernia development and recurrence. To date, only one genome-wide association study (GWAS) limited to inguinal hernia has been reported that identified four risk-associated loci. We aim to investigate polygenic architecture of abdominal wall hernia development and recurrence. Methods A GWAS was performed in 367,394 subjects from the UK Biobank to investigate the polygenic architecture of abdominal wall hernia subtypes (inguinal, femoral, umbilical, ventral) and id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
1
4
1
Order By: Relevance
“…Although the sample size for ventral hernia is relatively small, we observed that its genetic correlation was strong with multiple hernias. We noted that some correlation estimates were quite different from what was previously reported—for example, the reported genetic correlation between inguinal hernia and ventral hernia was 0.16; 20 however, it was estimated to be 0.53 in our analyses. The difference could be driven by the larger number of cases in our analyses.…”
Section: Resultscontrasting
confidence: 99%
“…Although the sample size for ventral hernia is relatively small, we observed that its genetic correlation was strong with multiple hernias. We noted that some correlation estimates were quite different from what was previously reported—for example, the reported genetic correlation between inguinal hernia and ventral hernia was 0.16; 20 however, it was estimated to be 0.53 in our analyses. The difference could be driven by the larger number of cases in our analyses.…”
Section: Resultscontrasting
confidence: 99%
“…Jorgenson and colleagues previously identified 4 inguinal hernia susceptibility loci purported to result in reduced MMP activity: WT1, EFEMP1, EBF2 and ADAMTS6 [13]. Recently, Wei et al replicated these associations and further implicated AIG1 and CALD1, which were identified as biologically relevant genes in their individual GWAS's of hernia phenotypes [15]. We have extended these results to focus on the shared biology of abdominal wall hernias.…”
Section: Plos Onementioning
confidence: 60%
“…The 1q41 locus (ZC3H11B) was strongly associated across three individual hernia phenotypes, the combined hernia cohorts, and importantly was also prioritised in metaUSAT meta-analysis. ZC3H11B, a zinc finger CCH domain-containing protein, was previously identified by Wei et al [15] in association with inguinal, femoral, umbilical and ventral hernia. ZC3H11B has also been associated with myopia endophenotypes, including axial length, refractive error, and corneal astigmatism [23].…”
Section: Genes Of Interestmentioning
confidence: 96%
See 1 more Smart Citation
“…The development and clinical implementation of polygenic risk score (PRS) is a core translational research focus of PMED. Initial efforts focused on prostate cancer PRS and its clinical validity in multiple ancestral populations ( Shi et al, 2021 ; Shi et al, 2022 ) and then expanded to additional conditions ( Ahmed et al, 2022 ; Wei et al, 2022a ; Glaser et al, 2022 ; Billings et al, 2023 ; Patel et al, 2023 ; Shi et al, 2023 ), including other cancer types ( Shi et al, 2019 ; Northcutt et al, 2021 ; Wei et al, 2022b ). Recently, our efforts have centered on the clinical implementation of PRS.…”
Section: Methodsmentioning
confidence: 99%